Nye namn på gammal grunn - Kruken, Kristoffer (NAMN OG NEMNE, 2019)
In Norway approximately one thousand dithematic names were coined in the years from 1870 to 1980. The coinage of new names was parallel to, and inspired by, the revival of old nordic names (Ê»the nordic name renaissance') in the same period. Many of the new names had a full nordic character, e.g. Dagbjørg and Dagbjørn. Others were compounds of a foreign first element and a nordic second element, e.g. Dormund and Jonhild. The growth of new names was at its height in the period 1890-1915, and most of the names arose in coastal and urban areas in the western and northern parts of the country. Often parents took one element from their own name to mark family renaming in line with the old nordic variation system. The lower and lower middle classes take a much greater part in the coinage process than the higher classes. There is no systematic correspondence between the making of new nordic names and the written language of the region (nynorsk or bokmål), contrary to a thesis sometimes put forward in Norwegian onomastic literature.